Tubular Apocrine Adenoma with Uncertain Malignant Findings: Report of a Case and Review of the Literature - Tokuchi, Keiko; Yanagi, Teruki; Maeda, Takuya; Nakazato, Shinichi; Miyamoto, Kodai; Tomaru, Utano; Anan, Takashi; Ujiie, Hideyuki (Case reports in dermatology, 2025)
Introduction: Tubular apocrine adenoma (TAA) is a rare sweat gland tumor, usually presenting as a well-defined, red to brown nodule on the scalp. Generally, TAA is considered as benign tumor; however, it may be difficult to differentiate TAA from metastatic or primary carcinoma. Case Presentation: A woman in her 90s presented with a pale red nodule on her right posterior auricle for 3 years. Histology showed several tubular structures contained two layers in the dermis. These showed decapitation secretion. At the periphery of the lesion, squamoid tumor cells formed nest-like patterns. Some squamoid tumor cells exhibited multinucleation. Based on the histopathological, immunohistochemical, and molecular biology findings, the tumor was diagnosed as TAA with undefined malignant changes. Conclusion: TAA is a rare sweat gland neoplasm. Although TAA is generally benign, it can exhibit aggressive features, making thorough pathological evaluation crucial to rule out malignancy.